Anticholinergic use trends in 14, 013 patients with schizophrenia from three national surveys on the use of psychotropic medications in China (2002–2012). (November 2017) - Su, Yun-Ai; Yan, Feng; Li, Qian; Xiang, Yu-Tao; Shu, Liang; Yu, Xin; Ning, Yu-Ping; Zhang, Ke-Rang; Li, Tao; Mei, Qi-Yi; Li, Ke-Qing; Si, Tian-Mei
Abstract: Our previous study demonstrated that there have been changes in the patterns of prescription antipsychotic use in China over the period from 2002 to 2012. The aim of this study was to evaluate whether time trends were present for the prescription of anticholinergic medications (ACMs) during the observation period. A total of 14, 013 patients with schizophrenia treated in 45 psychiatric hospitals/centers nationwide were surveyed in 2002, 2006 and 2012. Basic socio-demographic and clinical characteristics and the prescription of psychotropic drugs were recorded using a standardized protocol and data collection procedure. The frequency of ACM prescription was 25.9% in the whole sample (29.5%, 21.6%, and 27.4% in 2002, 2006 and 2012, respectively). In addition, different temporal trends were observed across age groups. Multiple logistic regression analysis of the entire sample showed that ACM prescriptions were predicted by females, outpatients, patients receiving high doses of antipsychotic medication, select study years, benzodiazepine users, patients displaying extrapyramidal side effects, as well as antipsychotic prescription patterns. Although there was more widespread use of second-generation antipsychotics over the past decade, the frequency of ACM use only slightly decreased. How to use ACM appropriately is still a therapeutic issue that needs to foster evidence-based prescription practice. Highlights: ACMs were used in more than one in four schizophrenia patients in China. Over the past decade, the frequency of ACM use decreased only slightly in China. The appropriate use of ACMs is still a therapeutic issue.